Placental Nutrient Transport and Intrauterine Growth Restriction - Gaccioli, Francesca; Lager, Susanne (Frontiers in Physiology, 2016)
Intrauterine growth restriction refers to the inability of the fetus to reach its genetically determined potential size. Fetal growth restriction affects approximately 5–15% of all pregnancies in the United States and Europe. In developing countries the occurrence varies widely between 10 and 55%, impacting about 30 million newborns per year. Besides having high perinatal mortality rates these infants are at greater risk for severe adverse outcomes, such as hypoxic ischemic encephalopathy and cerebral palsy. Moreover, reduced fetal growth has lifelong health consequences, including higher risks of developing metabolic and cardiovascular diseases in adulthood. Numerous reports indicate placental insufficiency as one of the underlying causes leading to altered fetal growth and impaired placental capacity of delivering nutrients to the fetus has been shown to contribute to the etiology of intrauterine growth restriction. Indeed, reduced expression and/or activity of placental nutrient transporters have been demonstrated in several conditions associated with an increased risk of delivering a small or growth restricted infant. This review focuses on human pregnancies and summarizes the changes in placental amino acid, fatty acid, and glucose transport reported in conditions associated with intrauterine growth restriction, such as maternal undernutrition, pre-eclampsia, young maternal age, high altitude and infection.